DIGITAL SOCIAL INNOVATION: A PRELIMINARY PORTFOLIO OF COMPETENCIES FOR SCHOOL SOCIAL WORKERS - Marzano, Gilberto; Lizut, Joanna; Ochoa, Luis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In this  article, the authors argue that professional experts are necessary who should also be educators, since they should work inside the school. Accordingly, cyber safety competencies should be included in the curriculum of school social workers in the same way as are competencies to sustain children with behavioral disturbance, support students with cultural and economic difficulties, provide the school community with psycho-social counselling, implement educational policies, etc. From the experience of running a training course for social workers in Poland on cyber threats, and from an ongoing research concerning digital social innovation within two EU funded projects, a preliminary portfolio of competencies has been defined and presented.